Influence of physical ageing on the electrical and swelling behaviour of ternary rubber vulcanisates - Nasar G M; Goman A S (Polymer Degradation and Stability, 1995)
The effects of pre-annealing ageing time at 70 C on the electrical properties (resistivity) and swelling behaviour in kerosene of a triblock rubber based on the blends of NR with different concentration ratios of both SBR and BR, all incorporating 40phr of high abrasion furnace carbon black, were investigated. It was found that the interspacing distance between carbon particles or aggregates was greatly affected by physical ageing and also by the rubber ratios in the test specimens. The degree of swelling in kerosene was found to decrease with the physical ageing and butyl rubber content of the specimen.
Source Year: 1996
Keywords: Physical ageing; Termary rubber vulcanisates